DEVELOPMENT OF SOLAR POWER PLANT AS SUPPORTING FACILITY FOR FISH FARMING IN KARANG PLOSO, PASURUAN - Prastio, Rizki Putra; Megantoro, Prisma; Mukhlisin, Agus; Abdillah, Sulthon Yusuf; Muda, Kemal Iskandar; Nurarsyah, Achmad Baihaqi; Farabi, Haikal; Sari, Feby Ananta; Abdillah, Waldi; Khadijah, Alyssa Rania (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
The freshwater fish farm, developed by the Maju Rukun community in Dusun Karang Ploso, Ngerong, has faced issues with slow fish growth and poor water quality after operating for seven months. These problems are caused by inadequate water circulation systems, resulting in a delayed growth process that normally takes only 3 to 4 months. The situation is exacerbated by poor drainage and high electricity consumption for a 0.5 HP (370 Watt) water pump. The water must be partially replaced with new water on a regular basis to maintain its quality. This procedure increases electricity consumption from the public grid or Perusahaan Listrik Negara (PLN) and raises operational costs by up to 80%, especially during the dry season. To address this issue, a community service project has been carried out to develop a 1.7 kWp hybrid Solar Power Plant. This system is designed to reduce reliance on PLN electricity and to provide additional energy for water circulation using solar panels and batteries. Additionally, this community service also includes training on how to operate and perform maintenance of the installed system for the Maju Rukun community and the locals. Implementing the hybrid power plant has significantly reduced electricity costs from PLN. Moreover, fish farm productivity has increased and contributed positively to the development of renewable energy technology in the fisheries sector.